Considerations for the reconfiguration of the Summer Olympic Games: Suggestions on the future of the Olympic Games - Amusa, L. O.; Toriola, A. L. (Journal of Human Movement Studies, 2005)
There is no doubt that the Olympic Games are by far the greatest sporting festival in the history of mankind. It is equally undeniable that the Games have helped to unite the peoples of the world (unity in diversity)- serving as a forum for the festival of humanity, friendship, solidarity and peace. The Games are the largest peaceful gathering of humanity, seeking to promote international understanding and dialogue among civilizations, nations and individuals. Clearly the Olympic Games continue to fascinate the world. It is a ereat concern that the noble ideas behind the revival of the games in l 896 have for some years now been put to test. Viewed from an historical perspective, there have been notable departures from the original ideals of the Games. Although the International Olympic Committee (IOC) has taken some positive steps to advance its agenda regarding the Games, there are serious problems and departures from the Olympic ideology that could result in diminished perception of the Organisation thereby causing it to lose its credibility. The purpose of this paper was to analyse critical issues concerning the reconfiguration of the Olympic Games and to give practical recommendations. In order to address the key issues, relevant literature was reviewed and analysed. Content analysis method was used to critique available literature. Based on the analysis the problems and challenges facing the organisation of the Summer Olympics were identified and discussed.